Le plus-que-parfait - expression d’antériorité et/ ou d’accompli? Essai d’analyse contrastive - Wydro, Barbara (Lingua Posnaniensis, 2010)
The Reichenbach's category of anteriority proves insufficient when we are trying to explain the uses of plus-que-parfait in French. In fact, this form has two functions: on the one hand PQP introduces events (system of infectum), on the other, consequences of events (system of perfectum). However, it is not always easy to decide, when analyzing texts, which is the right interpretation. The solution is to examine: 1. the narrative distinction between "first plan" and "second plan" (H. Weinrich's conception); 2. the phenomena of "flash-back".